The Relationship Between the Characteristics of Central Java Athletes in the Post-Sports Injury Recovery Period - Guntur Ratih Prestifa Herdinata; Aristiyanto; Fredy Eko Setiawan; Antonius Tri Wibowo (Jurnal Pendidikan Jasmani (JPJ), 2023)
This study aims to determine athletes' characteristics and the length of the recovery period after a sports injury. This research is cross-sectional; this sample is 50 athletes in an epidemiological study design that studies the relationship between athlete characteristics and recovery after sports injury. Based on statistical tests selected using chi-square with α = 0.05. Type of injury with lecture time 0.015 no relationship, Athlete age with lecture time 0.013 no relationship, Gender with lecture time 0.300 no relationship, Athlete nature with lecture time 0.001 no relationship, Training frequency with lecture time 0.348 no relationship, Length of competition with lecture time 0.050 no relationship, Player position with lecture time 0.297 no relationship, Playing techniques with lecture time 0.300 no relationship, Level of injury with lecture time 0.002 no relationship. This study concludes that there is a relationship between recovery time and age, athlete characteristics, and injury level. There is no relationship between recovery time and type of injury, gender, competition length, training frequency, player position, and playing techniques.